Injuries in Portuguese youth soccer players during training and match play - Brito, J.; Malina, R. M.; Seabra, A.; Massada, J. L.; Soares, J. M.; Krustrup, P.; Rebelo, A. (Journal of Athletic Training, 2012)
Abstract: Context: Epidemiologic information on the incidence of youth soccer injuries in southern Europe is limited. Objective: To compare the incidence, type, location, and severity of injuries sustained by male subelite youth soccer players over the 2008-2009 season. Design: Descriptive epidemiology study. Setting: Twenty-eight Portuguese male youth soccer teams. Patients or Other Participants: A total of 674 youth male subelite soccer players in 4 age groups: 179 U-13 (age range, 11-12 years), 169 U-15 (age range, 13-14 years), 165 U-17 (age range, 15-16 years), and 161 U-19 (age range, 17-18 years). Main Outcome Measure(s): Injuries that led to participation time missed from training and match play prospectively reported by medical or coaching staff of the clubs. Results: In total, 199 injuries reported in 191 players accounted for 14.6 ± 13.0 days of absence from practice. The incidence was 1.2 injuries per 1000 hours of exposure to soccer (95% confidence interval [CI] = 0.8, 1.6), with a 4.2-fold higher incidence during match play (4.7 injuries per 1000 hours of exposure; 95% CI = 3.0, 6.5) than during training (0.9 injuries per 1000 hours of exposure; 95% CI = 0.6, 1.3) (F1,673 = 17.592, P < .001). The overall incidence of injury did not increase with age (F1,673 = 1.299,P = .30), and the incidence of injury during matches (F 1,673 = 2.037, P = .14) and training (F 1,673 = 0.927, P = .44) did not differ among age groups. Collisions accounted for 57% (n = 113) of all injuries, but participation time missed due to traumatic injury did not differ among age groups (F3,110 = 1.044, P = .38). Most injuries (86%, n = 172) involved the lower extremity. The thigh was the most affected region (30%, n = 60) in all age groups. Muscle strains were the most common injuries among the U-19 (34%, n = 26), U-17 (30%, n = 17), and U-15 (34%, n = 14) age groups, whereas contusions and tendon injuries were the most common injuries in U-13 players (both 32%, n = 8). The relative risk of injury slightly increased with the age of the competitors. Conclusions: The higher incidence of injury during matches than training highlights the need for education and prevention programs in youth soccer. These programs should focus on coach education aimed at improving skills, techniques, and fair play during competitions with the goal of reducing injuries.